Effect of circadian clock disruption on type 2 diabetes - Tran, Hong Thuan; Kondo, Takeru; Ashry, Amal; Fu, Yunyu; Okawa, Hiroko; Sawangmake, Chenphop; Egusa, Hiroshi (Frontiers in Physiology, 2024)
Introduction Type 2 diabetes (T2D) is the predominant form of diabetes mellitus and is among the leading causes of death with an increasing prevalence worldwide. However, the pathological mechanism underlying T2D remains complex and unclear. An increasing number of studies have suggested an association between circadian clock disruption and high T2D prevalence. Method This review explores the physiological and genetic evidence underlying T2D symptoms associated with circadian clock disturbances, including insulin secretion and glucose metabolism. Results and Discussion Notably, circadian clock disruption reduces insulin secretion and insulin sensitivity and negatively affects glucose homeostasis. The circadian clock regulates the hypothalamic–pituitary–adrenal axis, an important factor that regulates glucose metabolism and influences T2D progression. Therefore, circadian clock regulation is an attractive, novel therapeutic approach for T2D, and various circadian clock stabilizers play therapeutic roles in T2D. Lastly, this review suggests novel therapeutic and preventive approaches using circadian clock regulators for T2D.